2022
DOI: 10.3390/infrastructures7020014
|View full text |Cite
|
Sign up to set email alerts
|

Failure Investigation of under Construction Prestressed Concrete Bridge in Chitwan, Nepal

Abstract: On 6 April 2021, a 200 m-long under-construction prestressed concrete bridge failed in the Chitwan District in central Nepal. Two of the four bridge spans collapsed without any notable evidence of dynamic force application. Under-construction bridge failures are sometimes reported and can have a significant impact on the future construction adjustments. Thus, a detailed study of failure mechanisms will be insightful for the structural engineering community. Aiming to document the failure modes and exemplify le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This section emphasizes the importance of reliability and validity in evaluating the quality and accuracy of survey questionnaire data. Reliability refers to the consistency and stability of the measurements, while validity measures how accurately the questionnaire assesses its intended purpose (Adhikari, 2022). High Cronbach's Alpha values indicate strong reliability of collected data.…”
Section: Reliability and Validity Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This section emphasizes the importance of reliability and validity in evaluating the quality and accuracy of survey questionnaire data. Reliability refers to the consistency and stability of the measurements, while validity measures how accurately the questionnaire assesses its intended purpose (Adhikari, 2022). High Cronbach's Alpha values indicate strong reliability of collected data.…”
Section: Reliability and Validity Of Resultsmentioning
confidence: 99%
“…A field survey typically involves direct interaction with participants. The study's population is unspecified, there is a lack of clarity about the target group or individuals (Adhikari, 2022).…”
Section: Reliability and Validity Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the four spans, three spans were designed as prestressed concrete girders and the third span from the right was designed as a steel truss bridge. Span# 1 and #2 from the right were collapsed after casting of concrete and before prestressing in April 2021 (Adhikari et al, 2022) [Span #2 appears to be reconstructed as shown in Figure 4 taken in October 2022]. Contractors that were habitual of relatively shorter spans could not adequately plan for relatively longer spans of the prestressed bridges.…”
Section: Prestressed Bridgesmentioning
confidence: 99%